Strategi Komunikasi Komunitas Gerakan Kesejahteraan Tunarungu Indonesia Dalam Menyosialisasikan Bahasa Isyarat Indonesia di Jakarta - Abdillah, Muhammad Farkhan; Andamisari, Dessy (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aimed to socialize Indonesian Sign Language, BISINDO (Bahasa Isyarat Indonesia), to the general public. Gerkatin (Gerakan Kesejahteraan Tunarungu Indonesia) Jakarta conducted this socialization effort to provide the public with fundamental information about the daily language of deaf individuals and to educate them about BISINDO. The ultimate goal was to foster more effective interaction and mutual understanding between hearing and deaf individuals. Employing qualitative research methods, this study collected data through in-depth interviews, observation, and documentation. The theoretical framework was based on Hafied Cangara's communication strategy theory for socializing BISINDO, encompassing the selection and setting of communicators and target audiences, the composition of message content, the choice of media or communication channels, and evaluation. The findings revealed that the communication strategy for enhancing effectiveness within the community regarding BISINDO socialization activities was suboptimal, evidenced by limited public interest and curiosity in learning the language. Additionally, BISINDO received minimal socialization through mass media, print media, or electronic media. Gerkatin Jakarta primarily delivered socialization messages for BISINDO through direct communication using educational methods, which is currently considered the most effective approach.